(untitled) (Jurnal Teknologi dan Informasi, 2020)
Orchid Forest is one of the educational tours located in Cikole, Indonesia. Orchid Forest is often used as the location of events. However, not much information about Orchid Forest is available on the internet. Promotion and information are limited to the Orchid Forest’s Instagram feed. To be able to get more information, the customers must contact or visit the Orchid Forest. Most of the customers of Orchid Forest come from out of town. Mostly they know Orchid Forest by word of mouth. Orchid Forest does not have any other media to expand the reach of its promotions, where customers can get adequate information about the procedures and costs of renting event locations in Orchid Forest. Therefore, it is necessary to design a website that can present adequate information about Orchid Forest. The system approach method used to analyze the system is an object-oriented approach and the system development method used is the waterfall. The design of the reservation information system is the aim of this study. The system was designed not only as a promotional medium but also as an information system that allows customers to make a reservation for event locations and payments through the website.